Student Motivation to Participate in Sports Interest and Talent Activities in the Psychology Department Nusa Cendana University - Manik, Grace Desmianta Blessias; Mage, Mernon Yerlinda C.; Takalapeta, Theodora (Universitas Nusa Cendana, 2024)
This study aims to describe the motivation of students to participate in Sports Interest Talent Activities (ITA) in the Psychology Study Program, Faculty of Public Health, Nusa Cendana University. Sports ITA in the Psychology Study Program is the most followed ITA by Psychology Study Program students. The number of students participating in Sports ITA is not in line with attendance during training, and students face obstacles that interest researchers in conducting research. This type of research is qualitative research with a phenomenological approach and in-depth interview techniques. The sampling technique uses purposive sampling techniques. Eight participants in this study participated in Sports Interest Talent Activities (ITA) at the Psychology Study Program Faculty of Public Health Nusa Cendana University. The study showed that hobbies, social support, and facilities at ITA Sports influenced student motivation. In addition, Sports ITA does not run well, so student motivation tends not to increase. The results of this study are expected to be an evaluation of the campus of the Program Faculty of Public Health Nusa Cendana University Psychology Study Program and Sports ITA to increase the motivation of students who participate in Sports ITA.